More than just an Anti-Infective Agent: A Prospective Pilot Clinical Trial to Determine the Effectiveness of IV Ertapenem in Severe Hidradenitis Suppurativa. (4th October 2017) - Ramesh, Mayur; Jayaprakash, Rachna; Hanna, Zachary; Gunasekaran, Kulothungan; Stein, Tricia; Abreu-Lanfranco, Odaliz
Abstract: Background: Hidradenitis suppurativa (HS) is a chronic debilitating cutaneous inflammatory condition caused by follicular occlusion/rupture with resultant inflammatory response. No durable control of HS is seen with current management strategies including topical and/or oral antibiotics, immunomodulatory drugs and local surgery. A recent French study using IV ertapenem for ≥4 weeks showed significant control of severe HS in patients (patients) who failed alternate medical strategies. We performed a prospective trial to study the effectiveness of IV ertapenem in severe HS. Methods: A prospective pilot clinical study was done at Henry Ford Hospital, Detroit from May 2013 to December 2015. All patients with severe HS (Hurley Stage III) and who failed medical management by Dermatology were referred to Infectious Diseases for daily IV ertapenem through a PICC line. Patients were followed up for at least 6 months after completion of therapy with weekly monitoring. Data including demographics, clinical response/adverse effects to ertapenem and any PICC line-related complications were recorded. Response to the treatment was based on clinical improvement in pain score/drainage and Hurley Staging of HS. Results: Twenty-three patients with severe HS consented to participate with a median age of 40 years (range 23–78 years) and 56% were female. Median treatment duration was 8 weeks (range 6–12). A 100% response rate was observed within 2 weeks of initiation and near complete resolution of active inflammation/drainage and improvement of pain score was observed in all patients at the end of treatment. Durable response was variable after completion of ertapenem (median 4 weeks; range 2–12); all subjects relapsed with varying degree of severity. In three patients who relapsed back to Hurley Stage III, ertapenem was restarted after 3 months with successful response. Adverse events include diarrhea (four patients), Clostridium difficile infection (one patient), and PICC line-related DVT (three patients). Clinical benefit despite ertapenem non-responsive bacteria in pretreatment culture of cutaneous drainage suggests an unproven immune-modulatory activity. Role of gut/skin microbial alteration needs further study. Conclusion: In selected patients with severe HS, IV ertapenem is highly effective in the control of inflammation and can be useful in combination with local surgery. Disclosures: All authors: No reported disclosures.